2017
DOI: 10.2147/opth.s127035
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, masked, in vitro comparison of three commercially available tear film osmometers

Abstract: PurposeThe purpose of this study was to compare the precision and accuracy of commercially available tear film osmometers.MethodsContrived tear solution target values representing the physiological range of tear osmolarity (normal eyes 297 mOsm/L, moderately dry eyes 342 mOsm/L, and severe dry eyes 383 mOsm/L) were constructed using a mix of mono- and divalent electrolytes, metabolites, serum albumin, and pH balanced to 7.4. Solution values were randomized and masked from the investigators during testing. Osmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…The results of this study reinforce a recent laboratory analysis of the TearLab and i-Pen 19. The data published by Rocha et al reported an average analytical CV of 1.6% for TearLab, which is essentially equivalent to the 1.3% CV for TearLab found in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study reinforce a recent laboratory analysis of the TearLab and i-Pen 19. The data published by Rocha et al reported an average analytical CV of 1.6% for TearLab, which is essentially equivalent to the 1.3% CV for TearLab found in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The i-Pen measures tear osmolarity via electrical impedance of the ocular tissues on the palpebral conjunctival membrane 18. Its utility has been questioned in the literature, as in vitro data suggest that the i-Pen provides insufficient performance to accurately and precisely delineate osmolarity levels in the physiological range 19. However, no data on the precision or performance of the device when testing tear fluid of human subjects, as per device labeling, is available in the peer-reviewed literature, and it may be that the technical implementation of the previous study did not accurately reflect the operative mechanism of the i-Pen device.…”
Section: Introductionmentioning
confidence: 99%
“…Osmometers produced by various manufacturers are used for examining osmolarity of the lachrymal film. In comparison with certain other instruments of a similar type, the instrument TearLab™ Osmolarity System (TearLab Corp., San Diego, CA) has high precision of osmolarity measurement [11,14], and is often used for the detection of pathologies linked with dry eye syndrome, or in the case of other diseases linked with a change of tear osmolarity (e.g. lagophthalmos) - [12].…”
Section: Resultsmentioning
confidence: 99%
“…Auch müssen viele andere Faktoren wie die Tageszeit, die Applikation von Augentropfen vor der Untersuchung wie auch klimatische Bedingungen bei der Bewertung der Ergebnisse berücksichtigt werden. Ebenso zeigt das neue I-Pen-Osmometer in durchgeführten Studien eine unterschiedlich gute Übereinstimmung der Osmolaritätsmessungen von vorbekannten Testlösungen [26,27]. Klinische Studien liegen mit diesem Gerät derzeit noch nicht vor.…”
Section: Diskussionunclassified